Rātchakitčhānubēksā. - Thailand (Krung Thēp : Samnakphim Ton Chabap, 1997)
Reproduction of Royal Thai Government gazette brought out during the reign of Chulalongkorn, King of Siam, 1853-1910.
lēm 1. Čhō̧.Sō̧. 1236 -- lēm 2. Čhō̧.Sō̧. 1237 -- lēm 3. Čhō̧.Sō̧. 1238 -- lēm 4. Čhō̧.Sō̧. 1239 -- lēm 5&6. Čhō̧.Sō̧. 1240-1241.
In Thai and some in English.
Keywords: Chulalongkorn, -- King of Siam, -- 1853-1910.; Gazettes -- Thailand; Law -- Thailand